Recent Publications (Quarterly Journal of Economics, 1936)
Recent Publications Get access The Quarterly Journal of Economics, Volume 50, Issue 4, August 1936, Pages 731–734, https://doi.org/10.1093/qje/50.4.731 Published: 01 August 1936